Interprofessional collaboration in the maternal care setting / Nur Zainie Abd Hamid and Siti Zaleha Abdul Rasid - Abd Hamid, Nur Zainie; Abdul Rasid, Siti Zaleha (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Recently, the rate of maternal mortality is unacceptably high, and it has been a main concern of the healthcare authorities. The increasing number of women’s deaths reported from preventable causes related to pregnancy and childbirth continues to bring concern in most effective ways out. Research argued, this was due to the lack of collaboration among healthcare professionals in which competencies are the potential contributor. This calls for interprofessional competencies to help strengthen existing healthcare teams. Therefore, the purpose of this research study is to determine the role of interprofessional collaboration competencies as a tool to improve the teamwork and collaboration effort among healthcare professionals in the maternal care setting. This quantitative study employs multi-stage random sampling of participants, who are the health professionals responsible for providing maternal care and services to women in the Maternity and Child Health Clinics in Malaysia. Established instruments with promising psychometric value are adapted to suit the current study setting. This study provides description of the current ability of healthcare professionals in the maternal care setting, particularly in Malaysia and identifies the aspects of collaboration that need to be improved and be given priority. This is done to ensure that, maternal health can no longer be compromised. It is hoped that, this is a starting point for the development of interprofessional collaboration programs by the regulators for both public and private sectors.